Analisis UX pada Aplikasi Komik Digital Menggunakan Metode Usability Testing - Nanda Asmara Ramdhan Putra; I Gede Arta Wibawa (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
The shift to digital media has intensified competition among comic applications, making User Experience (UX) a critical determinant of success. This study evaluates a digital comic app's UX via Usability Testing with five users , measuring effectiveness, errors, learnability, and satisfaction.Results indicate a 100% task completion rate , yet a high error rate of 60% reveals significant usability issues. The